Examining the Views of Muslim Philosophers about Psychological (Intrinsic) Egoism - Seyyed Jaaber Mousavirad (Comparative Theology)
Psychological egoism means that all human actions are done for the purpose of his own benefit and it is impossible for a person to do something only for the purpose of benefiting others. In this study, it is proved that the rule of "returning the purpose to the subject" accepted by Muslim philosophers is a kind of acceptance of psychological egoism. Then, in the next stage, this view is criticized and it is clarified that although the purpose of many human actions is the benefit that comes to himself (worldly or hereafter benefit), doing something only for the purpose of others cannot be considered logically impossible. In the case of God, although attributing the "ego" to God is not correct, it is possible to propose a kind of intrinsic egoism and intrinsic altruism regarding the divine nature. Based on this meaning, in this research, it is explained that Muslim philosophers have accepted a kind of intrinsic egoism concerning God, and based on this, they have considered it impossible for God to do something intrinsically to bring good and benefit to creatures. This idea is also explained in this study and it is criticized in such a way that it is never impossible that the act of God has a purpose outside of the essence that benefits only the creatures.